2005
DOI: 10.1097/01.ccm.0000186774.30674.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined administration of vasopressin, epinephrine, and norepinephrine during cardiopulmonary resuscitation in pigs*

Abstract: Vasopressin with or without epinephrine and norepinephrine resulted in higher myocardial and cerebral perfusion than epinephrine alone, but there was no benefit in adding norepinephrine to vasopressin and epinephrine with regard to cardiac and cerebral blood flow during cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
1
22
0
2
Order By: Relevance
“…This trigger for FFP is widely accepted (or implicit) in guidelines (16). They identified patients in whom an international normalized ratio of Ն1.5 was found during intensive care unit stay and evaluated FFP use in this subgroup for patients who were not actively bleeding.…”
Section: Was Sick and You Cared For Me-matthew 25:36mentioning
confidence: 99%
“…This trigger for FFP is widely accepted (or implicit) in guidelines (16). They identified patients in whom an international normalized ratio of Ն1.5 was found during intensive care unit stay and evaluated FFP use in this subgroup for patients who were not actively bleeding.…”
Section: Was Sick and You Cared For Me-matthew 25:36mentioning
confidence: 99%
“…[1][2][3] Animal studies, in contrast, have demonstrated superior survival rates with drug use. [4][5][6][7][8][9][10][11][12][13] One reason for failure of animal studies to translate to clinical practice may be the time at which the first drug is delivered. Previous work has demonstrated the average time to first drug administration in clinical trials is 19.4 minutes (range 13.3-25.0; 95% CI around the mean 12.8, 25.9).…”
Section: Introductionmentioning
confidence: 99%
“…19 Another study conducted, using a swine cardiac arrest model, concluded that vasopressin with or without epinephrine and norepinephrine resulted in higher myocardial and cerebral perfusion than with epinephrine alone. 20 In people, a recent meta-analysis showed that the combination use of both drugs led to significantly higher 24-hour survival rates. 21,22 The RE-COVER guidelines for ALS conclude that the use of vasopressin with or without epinephrine is a reasonable intervention during CPR.…”
Section: Discussionmentioning
confidence: 99%